Emergenza Covid19, tutela della salute e digitalizzazione: i limiti argomentativi della strategia digitale (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In this essay, we propose to deepen the arguments used in public communication to induce citizens to continue to cooperate and use digital tools as effective solutions during the pandemic. We will take as a case study the use of the contact-tracing app and we will analyse, through the scheme offered by the AMT –Argumentum Model of Topics, the communication strategies and the argumentative topics involved. The argumentative study will show the spread of a concept of law in which citizen tend to put aside their trust in others and seek an imperative legal solution.
Keywords: pandemic; argumentation; practical conflict; tracing-contact app; trust